An experimental study of precautionary bidding: conference paper - Kocher, Martin; Pahlke, Julius; Trautmann, Stefan T. (Jahrestagung des Vereins für Socialpolitik 2013, 2013)
Auctions often involve goods exhibiting a common knowledge ex-post risk. Precautionary bidding predicts that under expected utility, ex-post risk leads DARA bidders to reduce their bids by more than the appropriate risk premium. Because the degree of riskiness of the good, and bidders risk aversion, are difficult to observe in field settings, we conduct experimental auctions that allow to identify the precautionary premium directly. We find strong evidence for precautionary bidding, and bidders are better off when a risky object rather than an equally valued sure object is auctioned. The results are robust when controlling for potentially confounding decision biases. The current study provides the first empirical demonstration of precautionary motives in strategic settings.
Keywords: Graue Literatur; Konferenzschrift